Knowledge Sharing Behavior Of Business Teachers Of Pakistani Universities: An Empirical Testing Of Theory Of Planned Behavior - Hassan, Masoodul; Aksel, Ibrahim; Nawaz, Muhammad Saqib; Shaukat, Sadia (European Scientific Journal, ESJ, 2016)
This study aims to explain the knowledge sharing behavior of business teachers of Pakistani Universities using the theory of planned behavior. For this purpose, data was collected from 157 business teachers serving in the Pakistani Universities. Smart-PLS has been used to analyze the collected data. Factor analysis and Cronbach’s alpha confirmed the validity and reliability of the measurement scales. Similarly, Structural model were applied to find out the relationship among independent variables (attitude towards knowledge sharing, subjective norms of knowledge sharing, perceived behavioral control of knowledge sharing) and dependent variable (knowledge sharing intention and knowledge sharing behavior). The findings show positive and significant relationship among all the study variables.